The Effect of Reasoning Skills on Writing of Explanation Text Assessed from the Social Economic Status of Parents in Class VIII, SMP Negeri 2 Raya, Simalungun District, Indonesia - Jheni Yusuf Saragih; Abdurahman Adisaputera; Daulat Saragi (BIRCU, 2019)
Writing explanation text skills means the ability of students to express ideas, feelings, and experiences to others in writing a language that is good or contextual and true about social, natural and cultural phenomena. In relation to learning to write explanation texts, reasoning skills and socio-economic status of parents need to be considered. This study is aims to know the reasoning skills on writing explanation text skills reviewed by social economic status of parents of VIIIth grade students in junior high school 2 Raya, Simalungun District. This study is conducted by using Ex Post Facto approach. This study shows that there is a significant difference between explanation text writing skills of students who have high reasoning skills and those with low reasoning skills. It means that explanation text writing skills of students who have high reasoning skills are better results than explanation text writing skills of students who have low reasoning skills. The average score of writing skills produced by students having higher reasoning skills is higher than the explanation text writing skills of students who have low reasoning skills, that is 78.8> 73.2. Thus, in explanation text writing learning, students who have high reasoning skills are better results than students who have low reasoning skills.